ANALISIS KAPASITAS KELEMBAGAAN DAN AKUNTABILITAS KEPEMIMPINAN PERANGKAT DESA TERHADAP IMPLENTASI UU NO 6 TAHUN 2014 (Studi Kasus Pada Desa Kalisidi, Ungaran Barat, Kabupaten Semarang) - ririn vila wulansari; edi Santoso (Journal of Politic and Government Studies, 2017)
This paper describes the institutional capacity of the village government  and leadership accountability of village government in Kalisidi village, West Ungaran, Semarang regency to the implementation of UU No. 6 tahun 2014. UU No. 6 tahun 2014 envisioned the welfare of the villagers would be guaranteed by the Law . But in order to realize the ideals of UU No. 6 tahun 2014 was an important factor is the executive element that is ready for the task. Actor governance at the village level that is provided by the village governmentKey words: Institutional capacity, Leadership accountability, Implementation, UU no 6 tahun 2014